Practical challenges in applying The Place of Effective Management Test for Tax Residency in the context of South Africa's Headquarter Company Regime - Dumisa, Sinenhlanhla (Department of Commercial Law, 2023)
It is common for residency to be determined by place of incorporation or place of effective management (‘POEM'). As a result, the place of effective management test often results in two rival claims regarding taxation based on residency. Prior to 2017, paragraph 3 of article 4 of the OECD Model expressed that a non-individual ‘shall be deemed to be a resident only of the State in which the “place of effective management” is situated.' In 2017, the term ‘POEM' was abandoned, and the revised 2017 OECD Model now expresses that ‘the competent authorities of the Contracting States shall endeavour to resolve, by mutual agreement, cases of dual residence of a person other than an individual.' Most commentators interpret POEM as the point where key and commercial and strategic decisions are made. As such, a company headquartered in South Africa with a presence in other regional countries may have senior management based in South Africa and senior management in the regions, but may find the subsidiary restricted by the interpretation of POEM. The South African-headquartered company would be resident of South Africa if the key pronouncements were made by executives in South Africa. This study explores the practical challenges in the application and interpretation of the term ‘place of effective management' in tax treaties to establish the residency of South African headquartered companies investing in selected African jurisdictions. An analysis of the Mutual Agreement Procedure (‘MAP') is conducted, including in the form of a case study of Botswana and Lesotho. One of the challenges identified in the MAP is the lack of resources and empowerment to reach a resolution. Consequently, the OECD formed a forum to address the administrative and practical challenges by providing the competent authorities with adequate resources to individual agreements under negotiating the MAP, as well as to train employees. This study concluded that the test for residency should account for where the economic nexus is strongest. Future research could be conducted on the unique challenges that multinational businesses with a significant digital (but little physical) presence encounter, as well as value creation.